2017
DOI: 10.1111/imj.13403
|View full text |Cite
|
Sign up to set email alerts
|

Management of hypoxaemic respiratory failure in a Respiratory High‐dependency Unit

Abstract: Initial R-HDU management is an effective option in selected HRF to reduce ICU demand, although mortality and clinical deterioration despite NIV are more common than in HCRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…25 A diagnosis of AECOPD has been reported as the most prevalent diagnostic group in patients admitted to ICU with treatment limitations in Australian/New Zealand ICU with 9% having limitations imposed. The provision of NIV outside ICU is increasing internationally 27 but still uncommon in Australia, 28 although such service could both ameliorate resource constrains in ICU, improve triage decisions and extend the benefit of NIV to more AECOPD patients. The provision of NIV outside ICU is increasing internationally 27 but still uncommon in Australia, 28 although such service could both ameliorate resource constrains in ICU, improve triage decisions and extend the benefit of NIV to more AECOPD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A diagnosis of AECOPD has been reported as the most prevalent diagnostic group in patients admitted to ICU with treatment limitations in Australian/New Zealand ICU with 9% having limitations imposed. The provision of NIV outside ICU is increasing internationally 27 but still uncommon in Australia, 28 although such service could both ameliorate resource constrains in ICU, improve triage decisions and extend the benefit of NIV to more AECOPD patients. The provision of NIV outside ICU is increasing internationally 27 but still uncommon in Australia, 28 although such service could both ameliorate resource constrains in ICU, improve triage decisions and extend the benefit of NIV to more AECOPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 This study found a much higher prevalence of LOMT at 32% of admitted patients but it must be noted that this includes decisions made both at the time of admission and also during the ICU stay based on clinical progress. The provision of NIV outside ICU is increasing internationally 27 but still uncommon in Australia, 28 although such service could both ameliorate resource constrains in ICU, improve triage decisions and extend the benefit of NIV to more AECOPD patients. A recent Australian study demonstrated that ward-based provision of NIV achieved similar clinical outcomes while being more cost-effective, compared to NIV delivered in a high-dependency unit or ICU.…”
Section: Respectively Decreased Pao 2 and Hco 3 − And Increasedmentioning
confidence: 99%
“…However, 23% of patients with combined COPD and OSA may require bilevel positive airway pressure (BiPAP) for associated hypoventilation with hypercapnic respiratory failure (24). Hypercapnic (type 2) respiratory failure increases mortality (25), particularly in patients with COPD, even in those treated on a respiratory ITU (26). The COPD patient who suffered from a postoperative HCRF in our cohort may therefore have required non-invasive ventilation instead of CPAP and as such may not represent a lack of efficacy in peri-operative CPAP treatment.…”
Section: Clinical Significancementioning
confidence: 99%
“…
for their comments regarding our paper on hypoxaemic respiratory failure. 2 The authors disagree with their comments on protocol and data collection. The study was a retrospective, observational study utilising data from a comprehensive clinical database.
…”
mentioning
confidence: 98%